Exploring Students’ Self-Regulated Learning on Motivation in Learning New Vocabulary - Ramadhan; La Sunra; Musdalifah (International Journal of Language, Education, and Literature, 2026)
This study aims to explore the types, perceptions, and how self-regulated learning influences students' motivation when learning vocabulary. The researcher used a qualitative descriptive method to achieve the research objectives. Data were collected through semi-structured interviews. Participants in this study were twelve English Language Education students in the 2023/2024 academic year, who were selected purposively. Based on the results of the study, there are seven forms of self-regulated learning that students use in learning: learning from English podcasts on YouTube, learning from watching gaming YouTube content, learning from English songs, learning from watching English films, learning from OME TV, learning by posting vocabulary lists in easily visible places, and learn by English Message. Students also have various perceptions about self-regulated learning that help maintain their motivation when learning vocabulary, namely because they feel the positive impact of implementing self-regulated learning, remember their learning process, SRL makes their learning more enjoyable, they are motivated because their learning strategies are the same as their hobbies, and they are motivated because the strategies are easy to use. So, it can be concluded that self-regulated learning acts as an effective bridge between personal interests and academic goals, changing vocabulary learning from a passive effort into an active, autonomous, sustainable, and highly motivating process.